PERAN PEMERINTAH KELURAHAN HEGARSARI DALAM MEWUJUDKAN EFEKTIVITAS PROGRAM PEMULIHAN EKONOMI NASIONAL (PEN) UNTUK PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI MASA PANDEMI COVID-19 - Riza Purnama; Dika Alpiana (JURNAL DINAMIKA, 2022)
Based on the results of observations made, several problems were found related to the implementation of the distribution of UMKM assistance funds in order to support the national economic recovery in Hegarsari Village, Pataruman District, Banjar City, including (1) there were restrictions on UMKM activities so that the operating hours of UMKM actors became hampered (2) no direct socialization from the kelurahan party related to UMKM assistance funds (3) lack of supervision carried out directly by the kelurahan party in the utilization of UMKM assistance funds.The purpose of the study was to determine the effectiveness of the UMKM assistance program in Hegarsari Village, to find out the obstacles to the UMKM actors in the national economic recovery program, to find out the efforts made in overcoming the obstacles in the effectiveness of the national economic recovery program. The method used in this study is a qualitative approach with a descriptive method. Sampling technique with purposive sampling method. Collecting data using literature study techniques, observation, interviews and documentation. Data analysis with data reduction techniques, data presentation, and drawing conclusions. The results showed that the effectiveness of the program implemented was not in accordance with what was expected by UMKM actors in Hegarsari Village. Common problems that are still approaching are the pandemic and restrictions on trade activities. the existence of restrictions on trading activities, the majority of UMKM aid recipients prefer to use the capital for daily needs, so that the assistance program becomes less effective.